Gynecological malignancies in pediatric and adolescent group: a ten year experience in a national cancer center of Nepal - Sharma, KS; Pariyar, J; Misra, D; Mehta, S; Panthee, S (Nepalese Journal of Cancer, 2018)
Introduction: Gynecological malignancies in pediatric and adolescent group are common. Germ cell tumors and gestational trophoblastic neoplasia are the most frequently found malignancies which are highly chemosensitive. With prompt and appropriate treatment higher cure rate is attainable in such malignancies even in resource constraints country like Nepal.Objective: To study the clinicopathological profile and treatment outcome of gynecological malignancies among pediatric and adolescent group seeking treatment at B.P. Koirala Memorial Cancer Hospital (BPKMCH), Nepal.Methodology: Descriptive study was done at BPKMCH Nepal. All available case records of pediatric and adolescent girls diagnosed to have gynecological malignancies from 2002 to 2011 were collected and analyzed in terms of age, clinical features, malignancy types, treatment modalities and outcome.Results: Total 60 girls were eligible for the study. There were five patients (8.3%) below five years, 14 (23.3%) between 6-12 years and 41 (68.4%) patients between 13-19 years. Gynecological malignancies observed among the study group were: ovarian cancer in 46 (76.66%), gestational trophoblastic disease in 11 (18.33%), uterine cancer in two (3.33%) and vaginal cancer in one (1.66%). Among the ovarian cancers, 42 had malignant germ cell cancer (91.3%), three had epithelial ovarian cancer (6.5%) and one had juvenile granulose cell tumor. The commonest presentation was abdominal distension and pain in 70%. Onset of symptoms ranged from three days to 730 days (mean 95 days). Early stage disease was noted in 18 (30%) and advanced disease in 42 (70%). Eight (13.33%) underwent fertility sparing surgery only, 21(35%) underwent chemotherapy only and 31(51.66%) underwent multimodality treatment. Twenty (33.33%) defaulted and 40 (66.66%) completed treatment among which progressive disease and mortality was recorded in seven (17.5%) patients and 33 (82.5%) attended cure.Conclusion: Malignant germ cell cancer is the commonest gynecologic malignancy among pediatric and adolescent girls. In country where childhood marriage is still prevalent, GTT is also more common among adolescent girls. Early presentation and prompt appropriate treatment would offer chances of cure even with preservation of fertility.